Some features of short-term blood pressure variability in patients with arterial hypertension in comparison with healthy volunteers - Olena Kanishcheva (Актуальні проблеми сучасної медицини, 2022)
Introduction. Blood pressure variability is a significant prognostic factor and an independent predictor of cardiovascular disease and mortality in patients with arterial hypertension. Objective. The objective of our study was to perform a comparative analysis of blood pressure variability indices in patients with hypertension and healthy volunteers. Materials and methods. 172 patients with arterial hypertension and 22 healthy volunteers took part in the study. All study participants underwent daily BP monitoring, based on the results of which short-term blood pressure variability was assessed. The results. In this open, non-randomized, single-point study, we first performed a comparative analysis of short-term BP variability in patients with hypertension and healthy volunteers. Currently, there is no generally accepted consensus regarding which of the proposed indices of BP variability is more informative. Therefore, in order to objectify the obtained data, we calculated several of the most widely used indices of short-term BP variability. In the main group all indices, SBP as well as DBP, were higher compared to the control group. However, the statistical significance of this difference was confirmed only for some, not for all indices. Conclusions. According to the results of the analysis of SD, SDw, CV, SV and ARV indices, a higher variability of blood pressure was established in patients with arterial hypertension compared to that in healthy volunteers. On the other hand, convincing data on the diagnostic informativeness of the CV index in the assessment of blood pressure variability were not obtained in this study.